ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI MOBILISASI PROGRESIF TERHADAP PERUBAHAN STATUS HEMODINAMIK PADA PASIEN STROKE DI RUANG INTENSIVE CARE UNIT (ICU) - Ezzah Najlalya (2023)
Intensive Care Unit (ICU) is a special care unit provided for patients with critical or life-threatening conditions. The condition that often occurs in patients in the intensive care unit is hemodynamic instability, which is characterized by an increase or decrease in respiratory rate, mean arterial pressure, oxygen saturation, and heart rate from the normal range. Patients with stroke often require hemodynamic monitoring and special therapy. One of the non-pharmacological therapies that can be used to stabilize hemodynamics is passive range of motion (ROM) therapy. This study aims to determine the effectiveness of passive ROM therapy on changes in hemodynamic status of stroke patients in the ICU. The observed measurements of hemodynamic status included blood pressure, mean arterial pressure, pulse rate, respiratory rate, and oxygen saturation and were monitored through a bedside monitor. The results of the case study showed that there was a significant change in hemodynamic status in intervention patients who were given passive ROM therapy than control patients. It is hoped that passive ROM therapy can be used as a non-pharmacological treatment to stabilize hemodynamics in stroke patients in the ICU.